2000
DOI: 10.1007/bf02946104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding aFusarium poae extract and a natural zeolite to broiler chickens

Abstract: A feeding trial was conducted in order to determine the effects of aFusarium poae extract on the health and performances of broiler chickens and the possible protective effect of a natural zeolite. TheF. poae extract contained nivalenol, T-2 toxin and diacetoxyscirpenol and demonstrated high toxicity when administeredi.p. to rats. One-day-old broiler chickens were fedad libitum over a period of 28 days with the following diets: group I - control; group II - 0.5% zeolite; group III -F. poae extract; group IV-0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
5
7
0
Order By: Relevance
“…The results were in agreement with those in the literature (Dwyer et al, 1997;Keçeci et al, 1998;Curtui, 2000;Lotfollahian et al, 2004;Miles & Henry, 2007;Safaeikatouli et al, 2011). Altıner et al (2010) found that the total cholesterol levels of serum in laying hens fed rations with added microbial phytase and supplemented zeolites, were not considerably different.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results were in agreement with those in the literature (Dwyer et al, 1997;Keçeci et al, 1998;Curtui, 2000;Lotfollahian et al, 2004;Miles & Henry, 2007;Safaeikatouli et al, 2011). Altıner et al (2010) found that the total cholesterol levels of serum in laying hens fed rations with added microbial phytase and supplemented zeolites, were not considerably different.…”
Section: Resultssupporting
confidence: 91%
“…Conversely, Park et al (2002) indicated that blood cholesterol concentration was significantly lower in 3.0% natural zeolite treatments than in the control. Curtui (2000) also reported that zeolite supplementation in the diet (0.5%) caused a significant decrease in total protein in serum, and an increase in uric acid concentration, whereas some researchers (Lotfollahian et al, 2004;Safaeikatouli et al, 2011) observed increases in the total serum protein concentration by 3% zeolite supplementation. On the other hand, Pond & Yen (1983) and Ward et al (1991) found no effect of Na-zeolite A or clinoptilolite on blood urea nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…These variables in the present study, except ALT which had a significant quadratic contrast, were not significantly affected by the treatments, suggesting that dietary zeolite levels have no detrimental effect on fish health at least for gilthead sea bream. Similar findings were also reported by previous poultry and fish studies fed diets with varying zeolite levels (Curtui, 2000;Safaeikatouli et al, 2011;Vizcarra-Olvera et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…Serum triglyceride levels showed a linear increase with dietary zeolite elevation in the present study. Previous studies report no effect of dietary zeolite on triglycerides levels of chick and fish (Curtui, 2000;Tekeşoğlu, 2010). The increase in cholesterol and triglycerides with zeolite supplementation could be partly resulted from a linear increase in lipid retention by fish fed zeolite added diets (Kanyılmaz et al, 2015).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation